Temuan Mikroplastik pada Air di Instalasi Pengolahan Air 50 Liter per Detik Kamijoro Kabupaten Bantul - Utami, Inggita (Jurnal Riset Daerah, 2022)
Microplastics have been identified in all river sediments at Yogyakarta Province, one of which is the Progo River. The Progo River is used by the Bantul Regency Drinking Water Corporation (Perumda Air Minum) as raw water for the Kamijoro Installation. The purpose of this study was to measure abundance, classify microplastic characteristics (shape, size, color) and identify the type of microplastic polymer in the 50 liter per second Water Treatment Plant (WTP) as the installation with the largest capacity in Kamijoro. Around 250 mL of water samples were taken at the inlet (before treatment) and the outlet (after treatment) with 5 replications per point taken with an interval of 3 hours. The sample was filtered through a 5 mm diameter mesh sieve and given 30% H2O2 and saturated NaCl to remove organic compounds and make the supernatant suspected to contain microplastics floating on the surface of the water. The supernatant was filtered with filter paper and rinsed with distilled water and then stored in a petri dish. The collected microplastics were calculated visually with a binocular microscope and converted in units of particles per liter. The data were analyzed descriptively to compare the data on the inlet and outlet tubs. The abundance of microplastics obtained in the 50 liter IPA inlet tub sample per second was 3,372 particles/liter and was reduced by 70% at the outlet tub of 1,416 particles/liter. The dominant microplastic characteristics were found in water samples in the inlet and outlet, namely fiber, measuring 501-1000 µm in the inlet and outlet of 1-100 m, black in color, as well as polymers identified from the FTIR test results, namely polystyrene (PS) and polyamide (PA).